Non-Conscious Effect of Food Odors on Children’s Food Choices Varies by Weight Status - Marty, Lucile; Bentivegna, Héléna; Nicklaus, Sophie; Monnery-Patris, Sandrine; Chambaron, Stéphanie (Frontiers in Nutrition, 2017)
Objective: Food cues are omnipresent in the daily environment and may influence eating behavior even non-consciously. An increased reactivity to food cues, such as food odors, has been shown to be correlated with obesity in children. The objective of this study is to investigate whether the non-conscious influence of food odors on children’s food choices varies by their weight status. Methods: Seventy-four children, of whom 29 were obese, took part in this study. The children performed a food choice intention task presented as a computer game in which 30 pairs of food images (a fatty-sweet food picture vs. a fruit picture) successively appeared on the screen. The children had to choose the item “they most wanted to eat at the present moment” for each pair. While performing this task, the children wore a headset in which the microphone foam was odorized with a fruity odor, a fatty-sweet odor or no odor. They performed the intention task 3 times, one time for each olfactory condition. The odors were non-attentively perceived, i.e., none of the children were aware of the odorization of the microphone foams. The modelled probability is the probability to choose a fruit. Results: In children with obesity, the fruity odor increased the likelihood of a fruit to be chosen compared to the no-odor condition [OR (95% CL)=1.42 (1.13-1.78), P=0.0028], while the fatty-sweet odor had no effect on food choice [OR (95% CL)=1.07 (0.85-1.36), P=0.55]. In children without obesity, both the fruity and the fatty-sweet odors increased the likelihood to choose fatty-sweet foods compared to the no-odor condition [OR (95% CL)=0.76 (0.64-0.90), P=0.0015, for the fruity odor, and OR (95% CL)=0.79 (0.66-0.93), P=0.0062, for the fatty-sweet odor]. Conclusion: The different patterns of results obtained in both groups of children suggest differences in the mental representations activated by non-attentively perceived olfactory cues based on weight status.